Should we trust in leading indicators? Evidence from the recent recession - Katja Drechsel; Rolf Scheufele (Verein für Socialpolitik, 2010)
The paper analyzes leading indicators for GDP and industrial production in Germany. We focus on the performance of single and pooled leading indicators during the pre-crisis and crisis period using various weighting schemes. Pairwise as well as joint significant tests are used to evaluate single indicator as well as forecast combination methods. Moreover, we use an end-of-sample instability test to investigate the stability of forecasting models during the recent financial crisis. In general we find that only a small number of single indicator models perform well before the crisis. Pooling can substantially increase the reliability of leading indicator forecasts. In the crisis the relative performance of many leading indicator models increases. At short horizons survey indicators perform best and at longer horizons also financial indicators such as term spreads and risk spreads improve relative to the benchmark.
Keywords: C53; C22; E37; 330; Forecast Evaluation; Forecast Pooling; Structural Breaks